Corrected QT Interval Is Associated With Stroke but Not Coronary Heart Disease: Insights From a General Chinese Population - Guo, Xiaofan; Li, Zhao; Zhou, Ying; Yu, Shasha; Yang, Hongmei; Sun, Guozhe; Zheng, Liqiang; Lee, Byron K.; Pletcher, Mark J.; Sun, Yingxian (Frontiers in Cardiovascular Medicine, 2021)
Background: Prolonged heart rate-corrected QT (QTc) interval has been associated with incident cardiovascular diseases (CVD) in general Western populations. However, this association is unclear in Asian population. We aim to estimate the association between QTc interval and incident CVD in a general Chinese population. Methods: We analyzed 8,867 participants age ≥35 years and free of CVD at baseline in the Northeast China Rural Cardiovascular Health Study. A resting 12-lead electrocardiogram was performed on all participants, and QTc interval computed using the Framingham formula. Cox proportional hazards models were used to calculate hazard ratios (HRs) with 95% confidence intervals (CIs) for associations between QTc interval and incident stroke, coronary heart disease, and combined CVD events. Results: Over a median follow-up of 4.66 years, a total of 439 CVD events occurred (298 stroke cases and 152 CHD cases). After full adjustment, prolonged QTc defined by a sex-specific cutoff was associated with increased risk of developing stroke (HR: 1.82, 95% CI 1.20–2.75, P = 0.004) and combined CVD (HR: 1.52, 95% CI 1.05–2.19, P = 0.026). Spline analyses demonstrated no clear thresholds; when modeled as a linear relationship, each 10 ms increase of QTc interval was associated with an HR of 1.12 (95% CI 1.06–1.19, P < 0.001) for stroke and an HR of 1.10 (95% CI 1.05–1.15, P < 0.001) for combined CVD. Baseline QTc interval was not associated with incident CHD with either modeling strategy. Conclusions: Baseline QTc interval is associated with incident stroke and CVD in adults without prior CVD from a general Chinese population.